Antimicrobial susceptibility of microflora from ovine cheese - Kmeť, V; Drugdová, Z (Folia microbiologica, 2012)
Strains identified in ovine cheese and bryndza by matrix-assisted laser desorption/ionization time-of-flight analysis belonged to ten species of non-enterococcal lactic acid bacteria and included Lactobacillus casei/Lactobacillus paracasei, Lactobacillus plantarum, Lactobacillus rhamnosus, Lactobacillus helveticus, Lactobacillus delbrueckii, Lactobacillus fermentum, Lactobacillus brevis, Lactococcus lactis, Pediococcus pentosaceus and Pediococcus acidilactici. The susceptibility toward antibiotics was determined in lactobacilli, lactococci and pediococci and also in Escherichia coli for comparison. Analysis of L. fermentum and pediococci revealed the presence of non-wild-type epidemiological cut-offs in streptomycin, clindamycin or gentamicin. E. coli were resistant to ampicillin, tetracycline, enrofloxacin and florfenicol. No extended spectrum β-lactamases were detected.
Keywords: Cheese; Bacteria; Animals; antibakteriální látky; Anti-Bacterial Agents; Microbial Sensitivity Tests; ovce; Sheep; mikrobiální testy citlivosti; zvířata; sýr